Navigating life after multiple amputations: a qualitative exploration of rehabilitation and everyday challenges in Norway - Enersen, Nina; Løke, Daniel; Roaldsen, Kirsti Skavberg; Sviland, Randi (Frontiers in Rehabilitation Sciences, 2025)
PurposeMultiple amputations are a rare outcome following critical illness or injury, with significant impacts on the lives of those affected. This study aimed to explore and describe experiences of everyday life and municipal rehabilitation services among individuals with multiple amputations after their discharge from specialized rehabilitation in Norway.MethodsA qualitative research design was used with a lifeworld phenomenology perspective. Data were collected through individual, semi-structured interviews with five community-dwelling adults—one man and four women—who had multiple amputations, including at least one upper extremity. Data were analyzed using systematic text condensation.ResultFour categories emerged to describe the challenges of living with multiple amputations: “Navigating Dependence and Bodily Limitations”, “Challenges in Regaining Autonomy”, “Rehabilitation Challenges and Adjusting Expectations”, and “Adapting to a New Normal”.ConclusionParticipants experienced dependence, vulnerability, and a restricted lifeworld. The contrast between life with and without prosthetics underscores their vital role in autonomy. Unmet expectations of local rehabilitation services reveal structural barriers. The study highlights their experiences, advocating a lifeworld perspective to improve rehabilitation services.